(untitled) (Journal of Pathology of Nepal, 2018)
A 48-year-old male Caucasian, with no relevant medical history except for a mild depression, was found by the partner, passed out on the bedroom floor. Since he was found in cardiac arrest, cardiopulmonary resuscitation was attempted, without success. Initially, it was suspected to be a suicide attempt and autopsy findings revealed coronary atherosclerosis of about 40%, with no other recoverable cardiac findings. The brain showed multiple probable neoplastic lesions, associated with cerebral and cerebellar hemorrhage. The primary tumor was not identified, but the victim had multiple cutaneous nevi. Histological examination revealed melanoma metastases, confirmed by immunohistochemistry. In this case, the forensic autopsy allowed an accurate determination of the cause of death. Besides having fulfilled its role to the judiciary system, the autopsy also had relevance from an epidemiological point of view, which is essential for Public Health prevention programs.